Community-Led Health Education and Social Mobilization for Improving Stunting Prevention Behavior - Erik Kusuma; Ayu Dewi Nastiti; Dwining Handayani; R.A. Helda Puspitasari; Iis Rahmawati (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: Stunting remains prevalent in Indonesia’s coastal regions, where social norms and resource limitations hinder the implementation of preventive practices. In Tapa’an Village, Pasuruan, these challenges are compounded by the influence of extended family, unstable income, and restricted access to clean water. This study aimed to evaluate the effect of a community-led health education program combined with digital reinforcement on mothers’ stunting-prevention behaviors, using the Theory of Planned Behavior (TPB) framework.Method: A quasi-experimental one-group pretest–posttest design was conducted with 57 mothers of children under five. Data on attitude, subjective norms, perceived behavioral control, and behavioral intention were collected using validated questionnaires. Statistical analyses included paired t-tests and ANOVA to assess mean differences, and Pearson correlation to explore inter-domain relationships, chosen to capture both magnitude and interaction of behavioral change.Result : Significant improvements were found across all TPB constructs (p < 0.001) with large effect sizes (η² > 0.80). The most substantial change occurred in behavioral intention, driven by enhanced attitudes and social approval. Mothers described greater motivation, confidence, and collective encouragement after receiving digital reminders. The integration of participatory learning and digital cues effectively transformed individual awareness into a shared community practice. Digital reinforcement uniquely sustained motivation beyond group sessions, especially among digitally active mothers in extended families. Despite the design’s lack of a control group and short observation period, findings highlight the model’s potential for adaptation in coastal maternal health programs. Embedding digital reinforcement into Puskesmas activities could strengthen long-term stunting prevention efforts.